PENGEMBANGAN DAN PENERAPAN MEDIA MONOPOLY BERVISI SETS PADA BIDANG STUDI GEOGRAFI MATERI MITIGASI DAN ADAPTASI BENCANA SEBAGAI INOVASI DALAM PENDIDIKAN KEBENCANAAN - Andika Triwidada; Khairuddin .; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
The development and application of monopoly media is expected to build knowledge, skills and attitudes to encounter disasters. Integrated disaster education in the field of Geography studies, on the basic competencies of analyzing mitigation and adaptation to natural disasters. This research aims to describe the development and application of SETS visionary monopoly media in the field of geography studies on disaster mitigation and adaptation material. Media development uses a research design using the DDDMD approach (define, design, develop, manufacturing, disseminate), application using the control class approach and experimental class. As a result of the design development, Monopoly's visual media communication was 85.73%